Helsingfors Universitetsbibliotek – Konceptmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2024)
The model shows the negative spaces created by the ovoid shapes which characterises the building, carved in linden wood. The model is also to scale in order to showcase its sorrounding and its relation as an infill project. The site and surrounding buildings are made out of grey paper, where the Library directly contacts the surface is painted black. Located in the historically important Hirvi city block in the heart of Helsinki, the Kaisatalo, meaning Kaisa House, of the Helsinki University Library sits neatly between the old brick buildings. As the architecture office Anttinen Oiva Architects first major win in an open competition in 2008, the building serves as a central library for the previously dislocated faculties of the University of Helsinki. The competition entry name Avaus, meaning openings, summarizes the concept of the building. Despite having a very large program on a very small site, the architects successfully integrated the large ovoid openings into the building to let in natural light. When the ovoid shapes that create the openings intersect the facade, they create the arches that characterize the building, breaking the strict grid created by small windows in the brick facade.
Helsinki University library – Concept model
Keywords: bibliotek; library; infill project; female architect; kvinnlig arkitekt